2002
DOI: 10.1177/017084060202300101
|View full text |Cite
|
Sign up to set email alerts
|

The Co-evolution of Institutional Environments and Organizational Strategies: The Rise of Family Business Groups in the ASEAN Region

Abstract: In this paper we consider Southeast Asian Family Business Groups (FBGs) as a form of business enterprise as well as existing theoretical accounts of their behaviour. To do so, we develop and describe a co-evolutionary framework that incorporates notions of interdependence, path dependence, and 'system openness.' This co-evolutionary framework is used to anchor a case study describing the developmental paths of FBGs and their institutional environments. Because such neoevolutionary perspectives bring back into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 9 publications
2
93
0
Order By: Relevance
“…While farm and non-farm sectors have traditionally been considered as separate and distinctive, recent studies have demonstrated their similarities (Carter, 1996;Carter and Rosa, 1998;Alsos et al, 2011). One of the key similarities can be seen in the prevalence of entrepreneurial households that contain portfolios of interconnected businesses (Carney and Gedajlovic, 2002;Discua Cruz, Howorth and Hamilton, 2013), a feature which is as widespread in the non-farm sectors as it is in farm sectors (Carter and Ram, 2003;Ucbasaran et al, 2008).…”
Section: The Entrepreneurial Household: Connecting the Market And Thementioning
confidence: 99%
“…While farm and non-farm sectors have traditionally been considered as separate and distinctive, recent studies have demonstrated their similarities (Carter, 1996;Carter and Rosa, 1998;Alsos et al, 2011). One of the key similarities can be seen in the prevalence of entrepreneurial households that contain portfolios of interconnected businesses (Carney and Gedajlovic, 2002;Discua Cruz, Howorth and Hamilton, 2013), a feature which is as widespread in the non-farm sectors as it is in farm sectors (Carter and Ram, 2003;Ucbasaran et al, 2008).…”
Section: The Entrepreneurial Household: Connecting the Market And Thementioning
confidence: 99%
“…Broad agreement exists that BGs emerged as a response to underdeveloped institutions or 'institutional voids' (Khanna & Palepu, 1997) in developing economies, and that BG ties are beneficial in societies where such voids continue to exist (Carney & Gedajlovic, 2002). The institutional voids thesis states that BGs internalize activities that otherwise fail to materialize due to limitations in a society's financial, legal, and labor market institutions, which jeopardize the exchange of products and services between arm's length transactors (Leff, 1978).…”
Section: The Moderating Role Of Institutional Contextmentioning
confidence: 99%
“…The special issue in Organization Science (1999, number 3) reflects coevolution theory in strategic management and has stimulated a range of papers in different journals (e.g. Helfat and Raubitschek, 2000;Carney and Gedajlovic, 2002;Zollo and Winter, 2002) and once more a special issue in Organization Studies (2001, number 6).…”
Section: Strategic Managementmentioning
confidence: 99%